Nilai-nilai Islam dalam Tradisi Kamomoose Di Kecamatan Lakudo Kabupaten Buton - Hasaruddin Hasaruddin; Hendraman Hendraman (Al-Ulum, 2016)
Indonesia is the largest number of Muslim population in the world today. Therefore, different traditions carried out by its inhabitants. The Indonesians’ local traditions, subsequently, are inseparable with the values preserved in the teachings of Islam which the Qur’an or exemplified by the Prophet Muhammad. One tradition that is owned by the people of an Indonesia’s archipelago is kamomoose tradition. The tradition has been preserved by Lakudo community of Butonese of Southeast Sulawesi which is usually done once a year as an expression of gratitude for the gathering of the entire relatives who come on vacation to hometown. In the kamomoose event, the community members gather and mix together in one place regardless of class and social stratum. The tradition has been carried out from generation to generation and remains preserved until today. This tradition contains the values of Islam on local traditions in Buton, such as, pande–pandeaow, and nokalambemo.